Reconstruction of diffraction field from its samples distributed over space - (:unkn) unknown (Optical Society of America (OSA), 2015)
A new approach based on L1-norm minimization for accurate calculation of diffraction field from a set of sample points is presented. The proposed approach provides perfect reconstruction of the original diffraction field by using much fewer sample points taken over the space compared to an alternative one based on L2-norm minimization.